The Therapy of Desire : Theory and Practice in Hellenistic Ethics - Nussbaum, Martha C. (Martha Craven), 1947- (Book collections on Project MUSE., 2009)
The Epicureans, Skeptics, and Stoics practiced philosophy not as a detached intellectual discipline, but as a worldly art of grappling with issues of daily and urgent human significance: the fear of death, love and sexuality, anger and aggression. Like medicine, philosophy to them was a rigorous science aimed both at understanding and at producing the flourishing of human life. In this engaging book, Martha Nussbaum examines texts of philosophers committed to a therapeutic paradigm--including Epicurus, Lucretius, Sextus Empiricus, Chrysippus, and Seneca--and recovers a valuable source for o.